The Five-Finger Hypnosis Relaxation Technique in Reducing Anxiety Levels in Postpartum Mothers A Case Study - Novella Fahreza Firdaus; Diah Nur Anisa (MPI Press, 2026)
Introduction: Postpartum, or the puerperium period, is the phase that begins immediately after the delivery of the placenta and ends when the mother's reproductive organs return close to their pre-pregnancy condition. From a psychological perspective, postpartum mothers are at risk of experiencing anxiety due to role changes, concerns about the baby's condition, lack of experience in infant care, and hormonal changes that occur after childbirth. Globally, the prevalence of anxiety among women in the general population ranges from 3–8%; however, this prevalence can increase significantly during the postpartum period due to the adaptation to the new role as a mother. Prolonged anxiety can negatively affect the mother's quality of life and interfere with the breastfeeding process. One non-pharmacological intervention that can be applied is the five-finger hypnosis relaxation technique, which focuses on controlling thoughts and emotions through simple stimulation of the fingers. Objectives: This study aims to determine the effectiveness of the five-finger hypnosis relaxation technique in reducing anxiety levels in postpartum mothers. Method: This study used a descriptive case study method with a nursing care approach, which includes assessment, nursing diagnosis formulation, intervention planning, implementation of nursing interventions, and evaluation. The case study was conducted over one day on January 20, 2026, in the Firdaus Ward of ‘Aisyiyah Muntilan Hospital. Data analysis in this study employed a qualitative descriptive approach using three techniques: interviews, observation, and documentation study. Result: After being given the five-finger hypnosis relaxation technique for 30 minutes, the patient's anxiety level decreased, and the patient appeared calmer and more relaxed. Conclusion: The five-finger hypnosis relaxation technique is quite effective in reducing anxiety levels in postpartum mothers.